2018
DOI: 10.1155/2018/8503468
|View full text |Cite
|
Sign up to set email alerts
|

Human Neonatal Thymus Mesenchymal Stem Cells Promote Neovascularization and Cardiac Regeneration

Abstract: Newborns with critical congenital heart disease are at significant risk of developing heart failure later in life. Because treatment options for end-stage heart disease in children are limited, regenerative therapies for these patients would be of significant benefit. During neonatal cardiac surgery, a portion of the thymus is removed and discarded. This discarded thymus tissue is a good source of MSCs that we have previously shown to be proangiogenic and to promote cardiac function in an in vitro model of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Portions of the thymus gland are routinely removed during neonatal and infant cardiac surgery, and thus this tissue presents as an ample and untapped source of neonatal MSCs, which we have previously shown to have therapeutic effects. 29,59,62,63 The results of this study further support the ntMSC as an attractive candidate for cell therapy given their superior proangiogenic properties. Patients with congenital heart disease who undergo cardiac surgery in the neonatal or early infancy periods are at risk of developing medical conditions secondary to defective perfusion or angiogenesis, such as capillary rarefaction from ventricular pressure overload, which can contribute to heart failure, [64][65][66] cerebral damage from complications of cardiopulmonary bypass and cardiac surgery, 67,68 and myocardial ischemia and eventual heart failure from coronary obstruction after surgery.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Portions of the thymus gland are routinely removed during neonatal and infant cardiac surgery, and thus this tissue presents as an ample and untapped source of neonatal MSCs, which we have previously shown to have therapeutic effects. 29,59,62,63 The results of this study further support the ntMSC as an attractive candidate for cell therapy given their superior proangiogenic properties. Patients with congenital heart disease who undergo cardiac surgery in the neonatal or early infancy periods are at risk of developing medical conditions secondary to defective perfusion or angiogenesis, such as capillary rarefaction from ventricular pressure overload, which can contribute to heart failure, [64][65][66] cerebral damage from complications of cardiopulmonary bypass and cardiac surgery, 67,68 and myocardial ischemia and eventual heart failure from coronary obstruction after surgery.…”
Section: Discussionsupporting
confidence: 65%
“…57 A universal effect of exogenously transplanted MSCs is its ability to stimulate angiogenesis in the surrounding parenchyma, which may also contribute to the therapeutic effects of MSCs, especially in the setting of ischemia. 58,59 MSCs from a variety of tissues are being investigated as therapeutic agents, and our findings indicate that tissue source may be an important factor in determining their potency.…”
Section: Discussionmentioning
confidence: 84%
“…Research has been conducted to investigate the application of MSCs in 28-day old mice/rats for the treatment of heart diseases. In an in vitro experiment, it was found that neonatal thymus-derived MSCs (ntMSCs) secreted higher level of sonic hedgehog (Shh) in comparison to neonatal bone marrow-derived MSCs (nbMSCs) ( 63 ). Shh is involved in cell growth, cell specialization and morphogenesis of the corpus during embryonic development.…”
Section: Mscs For the Treatment Of Neonatal Heart Diseasesmentioning
confidence: 99%
“…Following these encouraging in vitro results, subsequent small animal studies showed that MSC had therapeutic efficacy in a MI model. Functionally, MSC were shown to have a number of positive effects including improving left ventricle function, increasing vascular density, decreasing scar size (López et al 2013;Wang et al 2018), left ventricle stroke volumes and ejection fractions (Dai et al 2005) and increasing remodelling of gap junctions (Dai et al 2005;López et al 2013;Wang et al 2018). There is also some evidence that MSC differentiate, in situ, into cardiac cells at sites of damage (Nagaya et al 2005).…”
Section: Large Animals Models For Treating Myocardial Disease Using Mscmentioning
confidence: 99%